Sosialisasi TPS 3R Sebagai Upaya Lingkungan Berkelanjutan Di Desa Sukoanyar Kecamatan Mojo Kabupaten Kediri - Halimah, Halimah; Yaswindra, Adelia Mutiara; Pujisetya, Noviana Eltanin; Khibtia, Rohmatul; Arif, Nadya Aulia Anindita; Widi, Ulil Nareswari; Aini, Laila Yuni Nur; Alvido, Geovany Hendra Ahkmad; Krisna, Moh Bayu; Maiyanti, Aziza Anggi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This study aims to provide education and understanding to the people of Sukoanyar Village regarding the dangers of littering and the negative impacts it will cause. The research method used is the ABCD (Asset Based Community Development) approach with five main stages, namely, Define, Discovery, Dream, Design, Destiny. Data collection techniques through interviews, observation, documentation and FGD (forum group discussion). The results of the activity indicate that the implementation of the 2025 Real Work Lecture (KKN) work program carried out in Sukoanyar Village can be a strategic step in efforts to build awareness and active participation of the community towards 3R-based waste management (Reduce, Reuse, Recycle). In addition, the community response to the 3R TPS socialization program implemented by the KKN 18 group in Sukoanyar Village has a positive impact. This is reflected in the high participation of residents, both in attendance and active involvement during the activity.